2022
DOI: 10.1177/07067437221136461
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Death From Physical Illness or Accidental/Intentional Causes Among Patients With Substance-Related Disorders

Abstract: Objective This study identified patient clinical and sociodemographic characteristics, and, more originally, service use patterns as predictors of death from physical illness or accidental/intentional causes. Methods A cohort of 19,015 patients with substance-related disorders (SRD) from 14 addiction treatment centers was investigated using Quebec (Canada) health administrative databases. Death was studied over a 3-year period (April 1, 2013, to March 31, 2016), and most predictors from 4 years to 12 months pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 69 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Prior studies have examined increased acute care utilization as a risk factor for mortality in patients with substance misuse [ 16 ]. Patients who visited the ED 1–3 times in the prior year for any medical reason had almost double the odds of mortality compared to those who did not [ 16 ]. In the same study, hospitalization in the previous year was associated with more than a ninefold risk of death.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior studies have examined increased acute care utilization as a risk factor for mortality in patients with substance misuse [ 16 ]. Patients who visited the ED 1–3 times in the prior year for any medical reason had almost double the odds of mortality compared to those who did not [ 16 ]. In the same study, hospitalization in the previous year was associated with more than a ninefold risk of death.…”
Section: Discussionmentioning
confidence: 99%
“…EMS utilization attributable to substance misuse is likely even higher when accounting for the substantially increased risk of critical care conditions, such as organ dysfunction, infection, and metabolic derangements [ 9 ]. Previous studies have demonstrated that frequent emergency department (ED) visits and repeat hospitalizations are important risk factors for poor outcomes among patients with substance misuse [ 16 ]. However, EMS is usually the first and often the only healthcare contact during an encounter requiring medical assistance in patients with substance misuse.…”
Section: Introductionmentioning
confidence: 99%
“…Those that have been conducted typically focus on all‐cause or specific causes of death (e.g. acute injury mortality [ 16 , 17 , 18 ]), or specific subpopulations of people presenting to health services with an alcohol‐related diagnosis (e.g. people with a non‐fatal injury with a comorbid alcohol use disorder diagnosis [ 19 ]).…”
Section: Introductionmentioning
confidence: 99%